KAJIAN SUBTITUSI AMPAS TAHU DAN PENGGUNAAN NATRIUM BIKARBONAT PADA PEMBUATAN TORTILLA (Jurnal Teknologi Pangan, 2013)
Tortilla is  a similar product  in  the  form of  chips  or corn chips made from a  flattened circular shape with sizes varying thickness. In order to diversify, Tortilla refined products and to enhance the nutritional  value. it  is  necessary  to substitute other  materials,  such  as tofu  waste  flour . The  tofu waste flour know still have a very good nutrient composition, especially protein and fiber. But with the substitution  of tofu  waste  flour know can reduce development and crispy Tortilla generated, so  the developer  needs  to  add  material  of  which  is  sodium  bicarbonate  (NaHCO3). This  study  aims  to determine  the  effect  of  substitution  and  addition  of  tofu  waste  flour  and  sodium  bicarbonate (NaHCO3) on  the  quality  of  physical,  chemical  and  organoleptic  Tortilla.  This  research  used Completely  Randomized Design (CRD) which are  arranged  in factorial which consist of two factors and  repeated  two  times. The  substitution  factor  is  the  tofu  waste  flour  10%, 20%, 30% and  the addition  of NaHCO3 factor II is 0.00%, 0.25%, 0.50%, 0.75%. The  best  results  were obtained  on substitution treatment with 10% wheat dregs out with the  addition  of 0.25% NaHCO3 to produce tortilla with water content of 9.016%, 74.884% starch content, crude fiber content of 2.046%, 7.924% protein  content,  yield  62.718%, 1.069  crispness  kg/cm2,  the  volume  of  20.346% and  the development of organoleptic value with a color ranking number 205, 215 flavor, aroma and crispness 204.5 147.